Harnessing digital voices for a greener future: the role of eWOM and information adoption in shaping green investment decisions - Dinh Duc Truong; Bui Thi Hoang Lan (Environmental Research Communications)
Purpose . This study aims to examine the influence of electronic word-of-mouth (eWOM) on green investment behavior in manufacturing enterprises, with a focus on the mediating role of information acceptance. The research responds to the growing need for sustainable business strategies and the increasing importance of digital communication in shaping corporate decision-making. Design/Methodology : The study integrates three theoretical frameworks: Elaboration Likelihood Model (ELM), Information Adoption Model (IAM), and Information Acceptance Model (IACM) to develop a comprehensive research model. Data were collected from 350 manufacturing firms in Vietnam through structured questionnaires. Structural equation Modeling (SEM) was employed to test the hypothesized relationships among variables. Findings : The results reveal that several eWOM components - such as information quality, credibility, need and attitude toward information-significantly affect GI behavior. Moreover, information acceptance mediates the relationship between eWOM and GI. However, information quantity was found to have no significant direct or indirect effect on GI. Implications and Recommendations : The findings suggest that managers should focus on improving the quality and reliability of digital information sources and foster a culture of proactive information engagement. Policymakers should enhance support for digital infrastructure and communication strategies to promote green transition in manufacturing. Originality/Value : This study is among the first to apply an integrated theoretical model (ELM-IAM-IACM) to examine how eWOM affects GI in the business context. It contributes both theoretically and practically by clarifying the information-processing mechanisms behind strategic investment decisions in the digital and sustainability era.